2008
DOI: 10.1136/jnnp.2007.124420
|View full text |Cite
|
Sign up to set email alerts
|

Greater occipital nerve block using local anaesthetics alone or with triamcinolone for transformed migraine: a randomised comparative study

Abstract: Adding triamcinolone to local anaesthetics when performing GONB and TPIs was not associated with improved outcome in this sample of patients with TM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(164 citation statements)
references
References 18 publications
4
152
1
7
Order By: Relevance
“…A placebo-controlled study of the benefits of GON block in chronic daily headache was positive. 4 Further study is warranted here, as intractable chronic daily headache is a significant health problem with little proven therapy.…”
Section: Greater Occipital Nerve Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…A placebo-controlled study of the benefits of GON block in chronic daily headache was positive. 4 Further study is warranted here, as intractable chronic daily headache is a significant health problem with little proven therapy.…”
Section: Greater Occipital Nerve Blockmentioning
confidence: 99%
“…Corticosteroid choices include triamcinolone or methylprednisolone. Ashkenazi et al 4 in 2008 reported a randomized double blind control study to address the usefulness of steroid addition to LA injections. The authors found that there was no difference in outcome between patients given greater occipital nerve blocks for headache with either 1) lidocaine and bupivicaine alone or 2) the same agents with the addition of a steroid medication; the severity of their headache and related symptoms were not significantly different between the two groups.…”
Section: Local Anesthetic Blockade: Overview Of Pharmacology and Genementioning
confidence: 99%
“…The major studies are summarized in Table 1 ( [51][52][53][54][55][56][57][58][59][60][61][62]. Unfortunately, there are very few controlled trials and no standardized methods were used for the selection of migraine patients (some had fixed unilateral headache, others not), the timing of infiltrations (ictal or interictal), the technique of infiltrations or blocks (unilateral or bilateral, association with blocks of other pericranial nerves or trigger point injections, one or more interventions), the compounds used for the blocks (local anesthetics alone or combined with different types and dosages of steroids) and particularly the evaluation of outcomes (number of headache-free days, variable percentage reduction of headache days or attacks, non-uniformly standardized pain indices).…”
Section: Infiltrations/blocks Of Pericranial Nervesmentioning
confidence: 99%
“…También la intensidad de la fotofobia y del dolor cervical, y en menor medida de la fonofobia, decreció de forma similar en los 2 grupos de pacientes. El periodo libre de dolor, el tiempo de respuesta y el uso de analgésicos no difirieron de forma estadísticamente significativa entre los que asociaban placebo o corticoides 29 . En el año 2001 se realizó el único ensayo clí-nico doble ciego disponible, controlado con placebo, para evaluar el bloqueo anestésico como fármaco preventivo en migrañosos.…”
Section: Discussionunclassified